Implementasi Pembelajaran Contextual Teaching And Learning Untuk Meningkatkan Kemampuan Penalaran Matematika Pada Pokok Bahasan Lingkaran (PTK pada siswa kelas VIII semester genap SMP N 3 Sawit Tahun 2014/ 2015) - Rismianti, Rismianti; , Prof. Dr. Budi Murtiyasa, M.Kom (2015)
This study aims to determine the increase in reasoning eighth grade students through the application of learning strategies Contextual Teaching and Learning on the subject of the circle. This type of research is the Classroom Action Research (CAR). Subject this study is students of class VIII E SMP Negeri 3 Sawit academic year 2014/ 2015 the number of students 30. The data collection method used is the method of observation, interviews, review of theory and tests. Data analysis techniques in this study conducted a qualitative descriptive. Qualitative descriptive analysis carried out by the method of flow. Data were analyzed since the act of learning, every action during the two rounds. The results of this research there is an increase in learning mathematics reasoning on the subject of the circle. It can be seen from the number of students who: 1) think coherently increased from 51,72% until 82,76%, 2) deliver precisely the argument increased from 44,83% until 79,31%, and 3) deduce an increased from 41,38% until 72,42%. The conclusion of this study is learning strategy Contextual Teaching and Learning can improve students' reasoning abilities in mathematics.